Practical Approach to the Management and Treatment of Venous Disorders - Sadick, Neil S.; Khilnani, Neil; Morrison, Nick (Springer London : Imprint: Springer, 2013)
This book shall assist the microscopist in a practical way, with the help of three mainstays, a. clinical information, b. the resources a standard histopathology laboratory may offer and c. the light microscope, to approach and solve the diagnostic problems he/she may face in the field of dermatopathology. In fact, this is the way in which the senior author of this book has been successfully working over thirty years in his capacity as director of a private dermatopathology laboratory.